2013
DOI: 10.3389/fnsys.2013.00100
|View full text |Cite
|
Sign up to set email alerts
|

A novel V1a receptor antagonist blocks vasopressin-induced changes in the CNS response to emotional stimuli: an fMRI study

Abstract: Background: We hypothesized that SRX246, a vasopressin V1a receptor antagonist, blocks the effect of intranasally administered vasopressin on brain processing of angry Ekman faces. An interaction of intranasal and oral drug was predicted in the amygdala.Methods: Twenty-nine healthy male subjects received a baseline fMRI scan while they viewed angry faces and then were randomized to receive oral SRX246 (120 mg PO twice a day) or placebo. After an average of 7 days of treatment, they were given an acute dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…On the other hand, weak AVP binding has been reported in the dorsolateral part of the basal amygdaloid nucleus(Loup et al 1991), raising the possibility that any AVP effects in the amygdala are due to its binding to its own receptor. Finally, these marginal effects of AVP could be related to dosage, since some published studies showing significant effects of AVP on brain activity use 40 IU (rather than 20 IU as used here) (Lee et al 2013; Zink et al 2011). In women, 20 IU intranasal AVP had no effect in either the anterior insula or the amygdala with either human or computer partners.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, weak AVP binding has been reported in the dorsolateral part of the basal amygdaloid nucleus(Loup et al 1991), raising the possibility that any AVP effects in the amygdala are due to its binding to its own receptor. Finally, these marginal effects of AVP could be related to dosage, since some published studies showing significant effects of AVP on brain activity use 40 IU (rather than 20 IU as used here) (Lee et al 2013; Zink et al 2011). In women, 20 IU intranasal AVP had no effect in either the anterior insula or the amygdala with either human or computer partners.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these studies did not compare data by sex. In healthy subjects, sex has been examined, and plasma AVP levels were positively correlated with distress in a pair‐bonded relationship in men, but not in women (Taylor, Saphire‐Bernstein, & Seeman, ) and recently it was shown that V 1A antagonists attenuated amygdala activation in response to aversive stimuli only in male subjects (Lee et al, ).…”
Section: Sex Differences In the Avp Systemmentioning
confidence: 99%
“…Acute pharmacological inhibition of V1aRs can produce anxiolytic effects while genetic deletion of V1aR produced both anxiolytic effects and reductions in social function in male mice (Bielsky et al, 2004). The modulation of both social behavior and anxiety by V1aR has sparked interest in its potential as a novel therapeutic target for stress-related psychiatric disorders, in which anxiety and social deficits can be comorbid (Lee et al, 2013; Meyer-Lindenberg and Tost, 2012). Currently it is unclear whether the effects of V1aR on social and anxiety-like behavior are mediated by independent or overlapping circuits.…”
Section: Introductionmentioning
confidence: 99%